Somatisms in the dialect world view of the Kuban subdialect speakers: A fulfilled cognitive potential - O.G. Borisova; L.Yu. Kostina (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper refers to the ideas of cognitive dialectology and studies the somatic cultural pattern in the dialect world view of the Kuban subdialect speakers. Idiographic presentation of phraseological units with a somatic component and detection of benchmark areas, which are interpreted by the Kuban subdialect speakers as having an anatomic focus on their body, revealed the cognitive specific character of somatisms in the Kuban phraseological units and paroemias. The obtained results prove the high level of corporeality in the world view of Kuban people. The word-building productivity of somatic vocabulary and its ability to form metaphors were demonstrated. The analysis of a whole variety of examples confirmed that the main functions of certain body parts often serve as the basis for representational apprehension of situations. The abstract reinterpretation of somatism makes it acquire a symbolic function instead of a nominative one. Specific cases illustrate certain constitutive characteristics of the dialect as a gnoseological and cultural phenomenon: pessimism, as well as parceling of cognitive objects, which are conceptualized in the dialect world view due to their importance to village residents. The most important result obtained is the detection of nation-wide and highly localized features in the implementation of the somatic code of the dialect world view of the Kuban subdialect speakers. The dialect features at the level of inner form of phraseological units were considered. Using phraseological units and paroemias, the view of the Kuban subdialect speakers on the linguistic situation in the region and the subethnical perception of Kuban Cossacks’ military routine were discussed.